1975
DOI: 10.1037/h0076915
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of reasons for resignation of professionals: Questionnaire versus company and consultant exit interviews.

Abstract: Three different information sources of reasons for voluntary resignation of professional employees in a large manufacturing company were evaluated: (a) exit interviews conducted by company management, (b) follow-up attitude questionnaires mailed from the company's personnel department, and (c) exit interviews by an outside consultant. Over 3 successive years, the distribution of reasons for termination derived from management exit interviews did not correlate significantly with data from the follow-up mail que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 1 publication
1
23
0
Order By: Relevance
“…Although prior research suggests that agreement may not be high (Hinrichs, 1975;Lefkowitz & Katz, 1969), this study provides a stronger test because a larger sample was used, a wider range of jobs was sampled, and data were obtained from supervisors as well as from personnel files and employees.…”
Section: Hypothesesmentioning
confidence: 99%
“…Although prior research suggests that agreement may not be high (Hinrichs, 1975;Lefkowitz & Katz, 1969), this study provides a stronger test because a larger sample was used, a wider range of jobs was sampled, and data were obtained from supervisors as well as from personnel files and employees.…”
Section: Hypothesesmentioning
confidence: 99%
“…Several studies have shown that exit interview and survey data, once collected, may be seldom used in many organizations (Garetson & Teel, 1982), the interview or survey is poorly administered (Woods & Macauley, 1985), and management receives incorrect feedback (Hinrichs, 1975). The most serious problem is that information may be distorted.…”
Section: Problemsmentioning
confidence: 99%
“…Another suggestion is to have a neutral non-threatening third party, such as an outside consultant, administer the interview or survey (Jurkiewicz, Knouse, & Giacalone, 2001). Indeed, research shows that exit information provided to management interviewers differs from that given to third party interviewers (Hinrichs, 1975). Still another suggestion is to pay exiting employees for participating.…”
Section: Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of Exit interviews cannot be undermined as it investigates the antecedents of turnover [13]. There have been arguments raised on the method and data gathered [14], [15], [16], and [17].…”
Section: Literaturementioning
confidence: 99%